KETERBACAAN TEKS DALAM BUKU â€œBAHASA INDONESIA WAHANA PENGETAHUANâ€ - Pramuwibowo, Ariesta Bagus (Jurnal Pena Indonesia, 2015)
The readability text in book â€œBahasa Indonesia Wahana Pengetahuanâ€ first revision (BIWPrp) in the Curriculum book 2013 had never been researched before reviewable from text quality and reader knowledge, besides that the text was very important in learning proceeding based on curriculum 2013. Because, the text Indonesian was model text for any subject. Therefore, it must be analyzed the level of readability text of Â book. This research diversiformed quantity-quality with descriptive method. Moreover, there were research result. First, the level of readability text was easy, 88%, based on the traits of effective sentence. Second, the level of readability text was difficult, 15%, based on the early knowledge of reader about the topic text. Third, the level of readability text was suitable for 7, 8, and 9 grades. Fourth, the level of readability text was difficult, 13%, based on the vocabularies control what clouted by the languagetion knowledge of VII grade student.